DERMATITIS PUSTULOSA CONTAGIOSA DE LOS CORDEROS - SAIZ MORENO, LAUREANO; CANADAS PEREZ, CRISTOBAL (My University, 1954)
no
CAMPO
Keywords: DERMATITIS PUSTULOSA, CONTAGIOSA, CORDEROS; CIENCIAS AGRARIAS; PRODUCCION ANIMAL; PORCINOS